2008
DOI: 10.1016/s0210-4806(08)73857-9
|View full text |Cite
|
Sign up to set email alerts
|

Comparación entre la posición de Valdivia y la posición prona en la nefrolitectomía percutánea (NLP)

Abstract: Valdivia position is as feasible as the prone position for PCNL. Success rates, as far as stone clearing, and complications are similar for both positions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(1 citation statement)
references
References 12 publications
(7 reference statements)
0
1
0
Order By: Relevance
“…Shoma et al [14] reported similar results for both positions (89% vs. 84%, respectively). Falahatkar et al [13] reported lower stone-free rates for both positions (77.5% vs. 80%, respectively), as did Amon-Sesmero et al [16] , at 76% vs. 74%, respectively. The complication rate related to our procedure was comparable to that in other studies.…”
Section: Discussionmentioning
confidence: 78%
“…Shoma et al [14] reported similar results for both positions (89% vs. 84%, respectively). Falahatkar et al [13] reported lower stone-free rates for both positions (77.5% vs. 80%, respectively), as did Amon-Sesmero et al [16] , at 76% vs. 74%, respectively. The complication rate related to our procedure was comparable to that in other studies.…”
Section: Discussionmentioning
confidence: 78%